Active Targeting Nanoparticle Self‐Assembled from Cisplatin‐Palbociclib Amphiphiles Ensures Optimal Drug Ratio for Combinatorial Chemotherapy. Issue 6 (23rd March 2021) - Xiang, Yucheng; Liu, Chendong; Chen, Liqiang; Li, Lian; Huang, Yuan
Abstract: Triple negative breast cancer (TNBC) not only exhibits aggressive progression and metastasis, but also responds to neither hormone therapy nor checkpoint blockade therapy. Thus, combinatorial chemotherapy is indispensable for TNBC treatment. However, due to the different pharmacokinetics of individual drugs and weak synergistic effects caused by random drug molar ratio in tumor, direct coadministration is far from satisfactory. Constructing a nanoscale drug delivery system with fixed drug molar ratios and maximum drug content is an urgent problem. Herein, an active targeting nanoparticle self‐assembled from cisplatin‐palbociclib amphiphiles with optimal drug ratio is reported. The combination of cisplatin and palbociclib at a molar ratio of 1:2 is found to have the best synergistic effect and is selected for follow‐up studies. After conjugating two palbociclib molecules to one cisplatin molecule, a fixed cisplatin/palbociclib (1:2) molar ratio is enabled and this amphiphilic conjugate can self‐assemble into nanoparticles. A small amount of iRGD coupled 1, 2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐N‐polyethylene glycol‐2000 (DSPE‐PEG‐iRGD) that further stabilizes the nanoparticle is introduced to fabricate the desired nanoparticle (iRGD‐PCN) and endow active tumor‐targeting ability. On an orthotopic TNBC mouse model, iRGD‐PCN efficiently accumulates in tumors and inhibits tumor growth. Additionally, the formation of lung metastasis nodes is also significantly suppressed. In general, the active targeting nanoparticles self‐assembled from cisplatin‐palbociclib amphiphiles provide options for combinatorial chemotherapy. Abstract : Active targeting nanoparticles self‐assembled from cisplatin‐palbociclib amphiphiles for combinatorial chemotherapy against triple negative breast cancer are fabricated. With multiple advantages such as facile preparation, fixed molar ratio of different drugs for best synergism, active tumor targeting, and high drug loading content, the nanoparticles reported in this study show great potential for future combinatorial chemotherapy.